HASIL BELAJAR IPS TERPADU MODEL TPS DAN TGT DENGAN MEMPERHATIKAN MOTIVASI BERPRESTASI - Rinda Doni Febriani; Pujiati Pujiati; Nurdin Nurdin (FKIP Unila, 2015)
The purpose of this study was to determine differences in learning outcomes IPS terpadu and the interaction between the model of student learning and achievement motivation. The method used is comparative with experimental approaches. The study population sample of 243 students with a number of 61 students were determined by cluster random sampling. Capturing data through documentation, questionnaires and tests. Hypothesis testing using two-way analysis of variance formula and t-test of two independent samples. The results showed: (1) there are differences in learning outcomes are taught using a model TPS and the students taught using TGT, (2) learning outcomes of students who are taught using a model TPS is higher than the TGT on high student achievement motivation, (3) learning outcomes students are taught using a model TPS is lower than the TGT on student achievement motivation is low, and (4) there is an interaction between the model of cooperative learning and achievement motivation Integrated Social Science subjects on learning outcomes.Tujuan penelitian ini untuk mengetahui perbedaan hasil belajar IPS Terpadu serta interaksi antara model pembelajaran dan motivasi berprestasi siswa. Metode yang digunakan adalah komparatif dengan pendekatan eksperimen. Populasi penelitian 243 siswa dengan jumlah sample 61 siswa yang ditentukan dengan Cluster Random Sampling. Pengambilan data melalui dokumentasi, angket dan tes. Pengujian hipotesis menggunakan rumus analisis varian dua jalan dan t-test dua sampel independen. Hasil penelitian menunjukkan: (1) terdapat perbedaan hasil belajar yang diajar menggunakan model TPS dan siswa yang diajar menggunakan TGT, (2) hasil belajar siswa yang diajar menggunakan model TPS lebih tinggi dibandingkan TGT pada siswa yang motivasi berprestasi tinggi, (3) hasil belajar siswa yang diajar menggunakan model TPS lebih rendah dibandingkan TGT pada siswa motivasi berprestasi rendah, dan (4) ada interaksi antara model pembelajaran kooperatif dengan motivasi berprestasi mata pelajaran IPS Terpadu terhadap hasil belajar.Kata kunci: hasil belajar, motivasi berprestasi, TGT, TPS